Investițiile chineze în zona Mediteranei de Est a Uniunii Europene - LUCIAN JORA (Revista de Știinţe Politice şi Relaţii Internaţionale, 2023)
The commercial routes along the Mediterranean are among the most important and trafficked in the world, at the intersection of three continents, a “bridge“ between Europe and Asia. The dynamics of foreign direct investments represent “the moment of truth“ in the relations between China and the European Union, respectively China and the states Eastern Mediterranean EU – Greece, Cyprus, Malta –, beyond the dynamics of political relations, policies, strategies or conjuncture political discourses. Beijing is investing in the area mainly in infrastructure, ports and railways, aimed at connecting the port terminals of Mediterranean Europe with the “heart“ of Europe, the priority destination point for Chinese exports. Some analyzes by analogy with WWII speak of Southern Europe and the Mediterranean as the „soft underbelly“ of Europe, for any power that later intends to expand towards the center of the continent, opinions that are not (so far) confirmed by the facts given that Chinese investments in the area are still small and in some countries negligible for a country with the size of China.